Determinants of neonatal mortality in the largest international border of Brazil: a case-control study - Suzana de Souza; Etienne Duim; Fernando Kenji Nampo (BMC, 2019)
Abstract Background Foz do Iguassu is a Brazilian municipality located in the most populous international border of the country and provides medical care to foreigners. Neonatal mortality in the city is higher than Brazil's average and corresponds to 61% of all deaths in children under five. The current study aimed to identify the determinants of neonatal mortality in Foz do Iguassu. Methods In this case-control study, we analyzed all neonatal deaths occurred in Foz do Iguassu from 2012 to 2016. Birth and mortality data were extracted from two national governmental databases (SINASC and SIM). We extracted data on (i) maternal sociodemographic characteristics, (ii) pregnancy care, and (iii) newborn characteristics. Multiple logistic regression with the conceptual framework was applied to examine the factors associated with neonatal mortality. Results Most of the deaths occurred in the early neonatal period (65.9%). The factors associated with neonatal death were fetal congenital anomaly (OR 22.49; CI 95% 7.44-67.95; p = < 0.001); low birth weight (OR 17.15; CI 95% 8.56-34.37; p = < 0.001), first minute Apgar score under 7 (OR 15.60; CI 95% 8.23-29.67; p = < 0.001); zero to 3 prenatal appointments (OR 3.34; CI 95% 1.28-8.73; p = 0.014) and prematurity (OR 3.60; CI 95% 1.87-7.11; p = < 0.001). Conclusion The high rate of neonatal death in Foz do Iguassu is strongly associated with newborn characteristics and not associated with maternal sociodemographic characteristics. Thus, the health services in the Brazilian side of this international borders should be aware of the quality of the prenatal care and childbirth attention provided.